2016
DOI: 10.1111/cge.12855
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial epileptic encephalopathy, 3‐methylglutaconic aciduria and variable complex V deficiency associated with TIMM50 mutations

Abstract: Mitochondrial encephalopathies are a heterogeneous group of disorders that, usually carry grave prognosis. Recently a homozygous mutation, Gly372Ser, in the TIMM50 gene, was reported in an abstract form, in three sibs who suffered from intractable epilepsy and developmental delay accompanied by 3-methylglutaconic aciduria. We now report on four patients from two unrelated families who presented with severe intellectual disability and seizure disorder, accompanied by slightly elevated lactate level, 3-methylglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
(28 reference statements)
2
33
0
1
Order By: Relevance
“…In contrast, the patient reported by Reyes et al () harbors a nonsense mutation (p.Ser122Ter) in one allele, encoding for a potentially truncated protein that is likely not expressed under physiological conditions, together with a missense mutation (p.Gly190Ala) on the other allele that maps to the conserved transmembrane domain of the protein. The clinical progression of our patient was also different and was similar to the initially reported TIMM50 patients, who also had missense mutations affecting amino acids of the intermembrane portion of the protein (Shahrour et al, ). In contrast, the patient of Reyes et al () showed a severe and rapid progression of the disease, leading to death at 2 years of age.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast, the patient reported by Reyes et al () harbors a nonsense mutation (p.Ser122Ter) in one allele, encoding for a potentially truncated protein that is likely not expressed under physiological conditions, together with a missense mutation (p.Gly190Ala) on the other allele that maps to the conserved transmembrane domain of the protein. The clinical progression of our patient was also different and was similar to the initially reported TIMM50 patients, who also had missense mutations affecting amino acids of the intermembrane portion of the protein (Shahrour et al, ). In contrast, the patient of Reyes et al () showed a severe and rapid progression of the disease, leading to death at 2 years of age.…”
Section: Discussionsupporting
confidence: 86%
“…Mutations in TIMM50 have been recently identified in three unrelated families (Reyes et al, ; Shahrour et al, ). The clinical and biochemical phenotypes of the previously described individuals were similar to those of the patient in this study, except that 3‐MGA‐uria was not observed in one of them (Reyes et al, ), and that cardiac involvement and neutropenia were not reported in any of the previous cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, partial depletion of Tim50 in yeast resulted in mtHsp60 import impairment without any effect on ACC (Yamamoto et al , ). Although a pathogenic mutation in human TIMM50 failed to be associated with import impairment (Shahrour et al , ), we noticed that Shahrour et al () used yeast as an in vivo model system to validate the mutation, despite the fact that human TIMM50 cannot rescue the phenotype of yeast ΔTim50 and the global conservation between these two proteins is very poor.…”
Section: Discussionmentioning
confidence: 83%
“…Sengers syndrome is an autosomal recessive disorder characterized by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy, and exercise intolerance caused by mutations in AGK (Aldahmesh et al , ; Mayr et al , ; Haghighi et al , ), encoding a protein only recently described as a component of the TIM22 complex (Vukotic et al , ). Finally, mutations in TIMM50 , coding for a core subunit of the TIM23 complex, have been reported in siblings from two unrelated families with severe intellectual disability and seizures, slightly elevated lactate levels, 3‐methylglutaconic aciduria and, in one subject, deficiency of mitochondrial complex V (Shahrour et al , ).…”
Section: Introductionmentioning
confidence: 99%